2016
DOI: 10.1186/s12877-016-0314-2
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the role of assistive technologies in the lives of people with dementia using objective care recipient factors

Abstract: BackgroundThe population of people with dementia is not homogeneous. People with dementia exhibit a wide range of needs, each characterized by diverse factors including age, sex, ethnicity, and place of residence. These needs and characterizing factors may influence the applicability, and ultimately the acceptance, of assistive technologies developed to support the independence of people with dementia. Accordingly, predicting the needs of users before developing the technologies may increase the applicability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 49 publications
(48 reference statements)
0
22
0
1
Order By: Relevance
“…Of the 22 studies in this category, twelve were undertaken in the UK, three in Australia [ 46 48 ], three in The Netherlands [ 49 52 ], two in Canada [ 53 , 54 ], one in the USA [ 55 ] and one in Sweden [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 22 studies in this category, twelve were undertaken in the UK, three in Australia [ 46 48 ], three in The Netherlands [ 49 52 ], two in Canada [ 53 , 54 ], one in the USA [ 55 ] and one in Sweden [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some of the 22 studies evaluated interventions falling clearly within the health domain (such as telehealth [ 57 , 58 ]; techniques/hardware used in hip fracture surgery [ 66 , 67 ]; screening for those at risk of lung cancer [ 68 ]; comprehensive assessment and personalised clinical management strategies to reduce incontinence and nocturia for older adults following hip fracture [ 53 ]; comprehensive assessment for frail older people receiving acute hospital care [ 56 ]; and a pharmaceutical product [ 55 ]. However, most of the studies that were identified evaluated interventions relating to care in a community setting/self-care and/or integrated services for those with chronic and long-term conditions, where broader elements of quality of life (such as maintaining independence) would be more obviously and/or directly affected; the interventions here included: integrated health and social care [ 49 , 52 ]; control over budgets for older people receiving community care in Australia [ 48 ]; a dementia self-management group [ 63 ]; a goal setting programme to promote healthy ageing and prevent dementia for those with low (or zero) needs [ 60 ]; information and communication technologies (ICT) training for those with a visual impairment [ 50 ]; interventions targeting post-acute needs [ 46 , 54 , 64 , 65 , 69 ]; and a programme of community activities aimed to help those with low (or zero) level needs to improve and maintain well-being [ 70 ]. Milne et al studied the impact of GPS devices for those with a cognitive impairment [ 15 ] and Boots et al assessed the impact of a blended care self-management program for family caregivers of people with early cognitive impairment [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Such models can be used as screening tools for those who will or will not be able to use the technological solution. Additionally, adoption modelling has been used to predict the needs of the user, prior to offering the solution with the aim of improving applicability and acceptance of assistive technologies (Czarnuch, Ricciardelli, & Mihailidis, 2016).…”
Section: Modelling Adoption Of Assistive Technologymentioning
confidence: 99%
“…MCS scores for carers in the 46-65 age group was signi cantly lower, this could be because carers within this age group are likely to be the "sandwich" generation [29], with responsibilities for caring for their own children and families whilst having to care for their aged parents. Previous research [9,34,35] has shown that there were fewer number of AT that met the needs of basic activities of daily living such as eating and bathing etc., which is con rmed by our survey. Basic activities of daily living, could be the tasks that a person with dementia is most dependent on [35] and carers living with persons with dementia are likely to be spousal carers and living with the person with dementia would mean carers being called on to physically assist them more often, this could explain why PCS scores were lower for carers living with the person with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research [9,34,35] has shown that there were fewer number of AT that met the needs of basic activities of daily living such as eating and bathing etc., which is con rmed by our survey. Basic activities of daily living, could be the tasks that a person with dementia is most dependent on [35] and carers living with persons with dementia are likely to be spousal carers and living with the person with dementia would mean carers being called on to physically assist them more often, this could explain why PCS scores were lower for carers living with the person with dementia. It has been reported earlier [36,37] that coping with care responsibilities and actual relationship with the person with dementia has a direct effect on carer quality of life, this is con rmed in our survey.…”
Section: Discussionmentioning
confidence: 99%